LEGAL ASPECTS AND UNCONVENTIONAL METHODS OF CANCER TREATMENT - S. V. Sidorov; N. Yu. Chernus (Сибирский онкологический журнал)
Background: The current legislation on the provision of medical assistance fixes the patient’s right to health care and medical assistance (Article 41 of the Constitution of the Russian Federation). Hence it follows that the patient has the opportunity to receive advice on the use of different treatment methods not only from his/her attending physician, but also from other doctors, to use available reference information, and to consider options for using methods of alternative medicine. Patients have the right to refuse treatment if they consider that the treatment options offered by the attending physician are inappropriate for them. Physicians have no right to treat patients without a patient’s informed consent. It is necessary to determine the actual legal model of the relationship between the attending physician and the patient, who may have different options for further treatment. The purpose of the study was to analyze the legislation on the protection of public health, which allows the attending physician to refuse further treatment of a patient, informing the chief physician about the reasons for the refusal.Results. In cases when cancer hospitals and centers refuse to treat patients who decline conventional cancer treatment and require alternative medicine instead, a signed mutual refusal of medical care is documented: the patient’s refusal of the treatment and the cancer institution’s refusal of the treatment options offered by the patient.